Comparative Investigation of Tongue and Esophagus Morphometry in Swiss Albino and Balb-c Mice - Osman Yılmaz; Yeşim Ayırtır Başdinç; Hüseyin Karadağ (Turkish Journal of Agriculture: Food Science and Technology, 2024)
This study was carried out to obtain morphometric measurement values of tongue and esophagus in Swiss Albino and Balb-c mice, to examine the biometric differences of these measurements between sexes and groups. Thirty-two mice, 16 Swiss Albino (8 males, 8 females) and 16 Balb-c (8 males, 8 females), were used for this study. Mice anesthetized with the ketamine-xylazine combination were fixed by the technique. The tongue and esophagus of the mice were carefully dissected and removed. Then, morphometric measurements of the dissected organs were taken, and statistical analysis was performed. When the morphometric measurement values were examined, it was seen that all of the measurement values obtained from both Swiss Albino and Balb-c mice were higher in males than in females. Statistically significant differences were observed between the groups in all morphometric measurement values of tongue and esophagus in both mouse races (p<0.05). Additionally, positive and significant correlations were found between morphometric measurement values of tongue and esophagus in both groups according to gender. Differences in morphometric measurement values of the tongue and esophagus were determined between genders and groups in Swiss Albino and Balb-c mice. Furthermore, this study provided basic morphometric data that will benefit various scientific fields related to the tongue and esophagus in these animals, especially anatomical studies.